THE USE OF TUTORIAL VIDEO TO IMPROVE STUDENTS WRITING OF PROCEDURAL TEXT (Experimental Study at SMP N 2 Padang Tiji) - Annisa, Annisa (Education Enthusiast : Jurnal Pendidikan dan Keguruan, 2021)
The aim of this research was to obtain the empirical evidence about the use of tutorial video to improvement students’ writing of procedure text. The method used in this research was a quantitative method and the research design was an experimental. The sample of this research was at the ninth grade of SMP 2 Padang Tiji academic year of 2019/2020. They were XI 1 class as the experimental class, whereas XI 2 class as the control one. Each class consisted of 23 and 20 students. The experimental class was taught with tutorial video while the control class was taught with teacher’s presentation or without tutorial video. For sampling technique the researcher used random sampling. The instrument used in this research was a written test and the scoring of writing rubric was used to score the students’ writing on the pre and posttest. Based on the calculation, the post-test mean scores of the experimental class was 88.39 while that of the control class was 61.95. Then, the result of statistical hypothesis testing by using independent sample t-test found that on degree of significance 5% (? = 0.05), t observe was 8.258 while t table was 2.021 or t observe > t table. Therefore, Ho was rejected and Ha was accepted. Furthermore, the Cohen’s formulation was used in order to know the effect size of tutorial video and the result was 2.52. It proved that tutorial video gave strong effect and it can be concluded that there was a significant improvement of tutorial video on students’ writing of procedure texts at the ninth grade of SMP 2 Padang Tiji in the academic year of 2019/2020.